Incomplete Preferences and Equilibrium in Contingent Markets. (5th November 2018) - Chambers, Robert; Melkonyan, Tigran
Abstract : This paper shows that betting or speculative trading between agents with incomplete preferences is likely to occur if agents have access to convex choice sets. This contrasts sharply with endowment economy models where preference incompleteness often hinders betting, speculative trading or mutually beneficial insurance arrangements. Our results imply that decision‐makers with identical tastes and identical feasible sets will potentially gain from speculative trade for generic status quo allocations. We also develop a framework for endogenizing the status quo allocations of decision‐makers that are treated exogenously in the existing literature. Finally, we provide a tractable differential representation of status quo allocations, equilibria and conditions where speculative trade may or may not emerge.